2021
DOI: 10.1002/jhet.4414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and molecular docking studies of quinoline‐conjugated 1,2,3‐triazole derivatives as antileishmanial agents

Abstract: In the present work, we have synthesized novel quinoline-conjugated 1,2,3-triazole derivatives 6a-l starting from substituted acetanilides in five steps. The synthesized compounds were screened for their antileishmanial activity. Quinoline-conjugated 1,2,3-triazole compounds 6c (IC 50 = 15.1 μg/ml), 6d (IC 50 = 14.6 μg/ml) and 6e (IC 50 = 14.3 μg/ml) displayed potent antileishmanial activity when compared with standard sodium stibogluconate (IC 50 = 14.3 ± 1.5 μg/ml). A molecular docking study against Leishman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Still, in 2021, another research group developed a series of twelve novel quinoline-1,2,3-triazole hybrids and evaluated them against L. donovani promastigotes, followed by molecular docking studies against L. major pteridine reductase ( Lm -PTR1) [ 67 ]. From their results, this research group was able to verify that three of the derivatives present significant levels of antileishmanial activity, with IC 50 values ranging from 29.55 µM to 31.05 µM, similar to the reference drug AmB.…”
Section: Quinolines As Antileishmanial Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, in 2021, another research group developed a series of twelve novel quinoline-1,2,3-triazole hybrids and evaluated them against L. donovani promastigotes, followed by molecular docking studies against L. major pteridine reductase ( Lm -PTR1) [ 67 ]. From their results, this research group was able to verify that three of the derivatives present significant levels of antileishmanial activity, with IC 50 values ranging from 29.55 µM to 31.05 µM, similar to the reference drug AmB.…”
Section: Quinolines As Antileishmanial Agentsmentioning
confidence: 99%
“…One year later, in 2022, Sabt et al developed a series of twenty quinoline-isatin hybrids and evaluated them for their antileishmanial activity against both L. major promastigotes and amastigotes ( Figure 32 ) [ 67 ]. Considering their activity against promastigotes, the results demonstrated that all the evaluated derivatives present considerable levels of antileishmanial activity with IC 50 values ranging from 0.51 ± 0.06 µM to 5.95 ± 0.28 µM, being more active than the reference drug miltefosine (IC 50 = 7.90 ± 0.26 µM).…”
Section: Quinolines As Antileishmanial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most adopted approaches for developing anti‐leishmanial agents are target‐based drug discovery and the repurposing of drugs. In Leishmania spp , numerous molecular targets have been explored in diverse metabolic pathways, allowing the discovery of new drug candidates; some are in the advanced stages of development [8] . Therefore, searching for molecules with anti‐leishmanial activity is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…In Leishmania spp, numerous molecular targets have been explored in diverse metabolic pathways, allowing the discovery of new drug candidates; some are in the advanced stages of development. [8] Therefore, searching for molecules with anti-leishmanial activity is still needed.…”
Section: Introductionmentioning
confidence: 99%